The Role of the Independent Campus Learning Program in Improving Quality of Higher Education Graduates - Iwan Asmadi; Zahra Zahra; Eneng Iviq Hairo Rahayu; Saddam Hussaen (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) program launched by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia is one of the breakthroughs in the Era of Digitalization in the field of Education, in order to prepare students to face social changes, culture, the world of work and rapid technological advances, student competencies must be prepared to be more in line with the needs of the times. Link and match not only with industry and the world of work but also with a rapidly changing future. Higher Education is required to be able to design and implement innovative learning processes so that students can achieve learning outcomes covering aspects of attitudes, knowledge, and skills optimally and always relevant.